Integrating dermatologists in primary care: impact on delays, patient and professional experiences - Maria Lovén; Amanda Eklund; Laura Huilaja; Markus Paananen; Paulus Torkki (BMC Health Services Research)
Abstract Background Primary healthcare centres are burdened by the management of patients with skin conditions, while general practitioners might lack the expertise to assess skin changes accurately. The traditional care chain for skin findings is a multistage process that can cause delayed diagnosis and treatment, distressing the patient. This study aimed to determine whether adding a dermatologist to the primary care team would streamline the care pathway of patients with skin conditions, while examining levels of satisfaction among patients and healthcare professionals. Methods A quasi-experimental multicentre study was conducted in three primary health centres in Finland. A dermatologist was integrated into two of the centres (intervention) but not the third (control). Data on timing of diagnosis and treatment and number of contacts were collected from records and analysed per care path. The Patient Enablement Instrument (PEI) and Net Promoter Score (NPS) were used to measure the patient’s experience of the appointment. NPS and professional satisfaction queries were used to measure professional satisfaction. Results In total 186 intervention and 176 control patients were included, with 38 primary care professionals. Compared with the control group, the intervention group showed a significantly shorter time to confirmed diagnosis and to treatment start (25 vs. 49 days, p < 0.001), with a higher proportion (49% vs. 27%, p < 0.001) receiving immediate treatment in the primary care setting. Patients in the intervention group required fewer visits. Patient experience by PEI and NPS scores were higher in the intervention group (p ≤ 0.022 for each). Satisfaction levels among professionals in both groups were higher after the intervention than before, although the NPS score did not improve significantly in the control group. Almost all professionals advocated for the continuation of the integrated care pathway. Conclusions The integration of dermatologists into the primary care streamlined the management of skin conditions from diagnosis to treatment, while improving the experiences of both patients and healthcare professionals. This integrated care path is beneficial for the management of patients with skin findings in primary care.